1976
DOI: 10.1128/jb.127.1.334-340.1976
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan synthesis and turnover in cell division mutants of Agmenellum

Abstract: The synthesis and turnover of peptidoglycan in Agmenellum quadruplicatum was investigated using D-LU-'4C]alanine followed by proteolytic digestion. The rate of turnover of alanine in the peptide portion of the peptidoglycan was measured in strain BG-1 and in two division mutants of this strain: one was blocked in cell separation; and the other was a low-temperature, conditional cell division mutant. The peptide portion of peptidoglycan turned over in all three strains tested, but no correlation was observed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Bacillus subtilis and Neisseria gonorrhoeae lose 50% per generation (16,23,24); Lactobacillus acidophilus loses 30% per generation (5); and Staphylococcus aureus, B. megaterium, and B. cereus lose 12 to 18% per generation (8,23,33). Blue-green algae lose 16 to 26% of the muramyl peptide per generation (11). E. coli and Streptococcus faecalis lose no muramyl pentapeptide per generation during exponential growth (5, 9, 31).In Staphylococcus, Lactobacillus, and Bacillus species, varying the periods of incubation with the radioactive precursor showed that the more newly synthesized wall was less likely to be utilized than the older portions of the wall.…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus subtilis and Neisseria gonorrhoeae lose 50% per generation (16,23,24); Lactobacillus acidophilus loses 30% per generation (5); and Staphylococcus aureus, B. megaterium, and B. cereus lose 12 to 18% per generation (8,23,33). Blue-green algae lose 16 to 26% of the muramyl peptide per generation (11). E. coli and Streptococcus faecalis lose no muramyl pentapeptide per generation during exponential growth (5, 9, 31).In Staphylococcus, Lactobacillus, and Bacillus species, varying the periods of incubation with the radioactive precursor showed that the more newly synthesized wall was less likely to be utilized than the older portions of the wall.…”
Section: Resultsmentioning
confidence: 99%